A Novel Rotary FMCW Radar for Omnidirectional Multiperson Localization and Vital Signs Detection - Wang, Zibin; Li, Chengguang; Tu, Silong; Liu, Zhenyu (IEEE transactions on microwave theory and techniques, 2024)
Omnidirectional multiperson localization and simultaneous vital signs detection are challenges for the single radar system. A novel rotary radar based on frequency-modulated continuous-wave (FMCW) modulation is proposed to achieve omnidirectional exploration. The model of this radar is brought out to simultaneously locate multiple persons and detect their vital signs in all directions. However, the human torso width that will cross some fan-shaped recognition areas of the radar brings difficulties for precise localization. In addition, because the intensity of vital signs contributed by different torso parts is diverse, the detection performance of the respiration rate (RR) and heartbeat rate (HR) are affected. To this end, an energy aggregation analysis (EAA) is proposed to select sector and range-bin for human localization. Moreover, a multicell correlation fusion (MCF) method is presented to improve the performance of RR and HR, by merging the reflected intensity of different torso parts. Experimental results have shown the feasibility and practicability of the proposed methods. EAA is proven to enhance the ability of multiperson localization, and MCF is verified to improve the SNR of RR and HR. Furthermore, the multiperson experiment shows that the locations and vital signs of multiple subjects in different directions can be obtained simultaneously.